Eco-Friendly Au@Al-MOF Nanocomposites Fabricated with Eleutherine bulbosa Extract for Mercury Detection in Cosmetic Product - Rosmainar, Lilis; Kumalasari, Meiyanti Ratna; Beladona, Siti Unvaresi Misonia; Ayuchecaria, Noverda; Andreani, Agustina Sus (Applied Science and Engineering Progress, 2026)
Mercury (Hg²⁺) contamination in cosmetics, particularly skin whitening products, poses significant public health risks due to its well-documented toxicity and bioaccumulative nature. This study reports the development of an environmentally benign colorimetric sensor for Hg²⁺ detection by incorporating gold nanoparticles (AuNPs) within aluminum-based metal-organic frameworks (Al-MOF), utilizing Eleutherine bulbosa extract as a green reducing agent. Extensive characterization (XRD, FTIR, TGA, TEM, SEM, FESEM) verified successful AuNPs incorporation (average diameter 25.96 nm) while maintaining MOF structural integrity. Spectrophotometric analysis revealed a distinct red shift in surface plasmon resonance from 541 nm (pristine AuNPs) to 548 nm (Au@Al-MOF), confirming strong interactions between the AuNPs and the MOF framework. The sensor exhibited exceptional Hg²⁺ selectivity with minimal cross-reactivity to interfering metal ions, achieving a 3.46 ppm detection limit and 54-day stability. Validation studies using commercial skin whitening creams demonstrated excellent correlation between the UV-Vis method (4.53 ppm Hg²⁺) and atomic absorption spectroscopy (4.59 ppm), with 98.7% agreement (±1.3% variance), confirming method reliability. These findings establish Au@Al-MOF as a robust, sensitive, cost-effective colorimetric platform for Hg²⁺ detection. The technology holds significant potential for integration into other heavy metal detection systems and portable devices, addressing critical needs in cosmetic safety, environmental monitoring, and food quality control.